(untitled) - Briggs, D. | (Cambridge, 1984)
Natural populations of plants show intricate patterns of variation. European botanists of the eighteenth and nineteenth centuries used this variation to classify different "kinds" into a hierachy of family, genus, and species. Although useful, these classifications were based on a belief in the fixity of species and the static patterns of variation. Darwin's theory of evolution changed this view; populations and species varied in time and space and were part of a continuing process of evolution. The development of molecular techniques has transformed our understanding of microevolution and the evolutionary history of the flowering plants. This revised, extended edition describes the historical background to plant variation studies and considers the remarkable insights that molecular biology has recently given into the processes of evolution in populations of cultivated, wild and weedy species; the threats of extinction faced by many endangered species and the wider evolutionary history of the flowering plants as revealed by cladistic methods
Keywords: Plants,Plants; Variation,Evolution